Democratic Republic of Sao Tome and Principe : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper for the Democratic Republic of Sao Tome and Principe (STP) underlies the recent upward trend in inflation that was heavily influenced by external factors. The policy mix to achieve price stability requires effective control of money supply and fiscal restraint. As in other developing countries, operational targets for monetary policy need to be considered, taking into account STP's specific circumstances. Weak financial intermediation limits the effectiveness of some monetary instruments such as short-term interest rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet